Preliminary study of the phytoconstituents of Pleurotus ostreatus grown in coffee pulp waste - Collantes Díaz, Ingrit Elida (2020)
The mushroom Pleurotus ostreatus also called oyster mushroom is widely cultivated for its nutritional value, as well as, for its different health benefits and for its values in remediation. Laboratory N° 11 of the Universidad Nacional de Ingeniería of Peru is cultivating P. ostreatus making use of residues of coffee pulp as a substrate. The present work describes the identification of the major phytoconstituents in the apolar fractions of the organic crude extrac of oyster mushroom. After the transesterification of a fraction rich in fatty acids, the palmitic acid methyl ester was identified as the majority and of a second fraction were identified of the steroids 5α,8α-epidioxi-24(R)-metilcolesta-6en-3β-ol and 5α,8α-epidioxi-22E-ergosta-6,22-dien-3β-ol. The compounds were identified by gas chromatography analysis coupled to a mass spectrometer and by nuclear magnetic resonance of hydrogen and carbon 13.